Mungbean (Vigna radiata L. Wilczek) as Functional Food, Agronomic Importance and Breeding Approach for Development of Climate Resilience: Current Status and Future Perspectives - Sehrawat, Nirmala; Yadav, Mukesh; Sharma, Anil Kumar; Kumar, Sunil; Singh, Manoj; Kumar, Vikas; R, Rakesh; Sharma, Pooja; Singh, Raj (Asian Journal of Biological and Life Sciences)
Mungbean (Vigna radiata L. Wilczek) is highly nutritive food, important feed and fodder crop throughout the world. It is an excellent source of nutrients, minerals and vitamins. Seeds and sprouts of mungbean are commonly used in form of healthy diet. This crop is of particular interest for the countries suffering from low protein diet and mal nutrition. Unfortunately, it is highly sensitive towards climate variability and environmental stress factors. Salinity stress is highly prevailing factor at global level which drastically limiting mungbean production. Huge proportion of arable land has been converted into saline and is continuously increasing every year. Besides this, large population size, deprived availability of nutritious food and lack of improved mungbean varieties against salinity raises serious concern towards food and nutrition security. Small genome size, narrow genetic base and poor exploration of available germplasm for valuable traits further restricts genetic improvement of this crop. In present scenario, the introduction of useful genes from exotic into the cultivated environment through hybridization is more promising to develop climate resilient crops. Presence of bioactive compounds in mungbean providing various health benefits has increased the scientific interest in this crop.
Keywords: Breeding; Food security; Germplasm; Health benefits; Mungbean importance; Salinity